Role of the Clinical Nurse Specialist in Improving Patient Outcomes After Cardiac Surgery. (January 2015) - Soltis, Lisa M.; Tracy, Mary Fran
<x xml:space="preserve">Abstract</x> Health care reform continues to focus on improving patient outcomes while reducing costs. Clinical nurse specialists (CNSs) should facilitate this process to ensure that best practice standards are used and patient safety is enhanced. One example of ensuring best practices and patient safety is early extubation after open heart surgery, which is a critical component of fast track protocols that reduces may reduce the development of pulmonary complications in the postoperative period while decreasing overall length of stay in the hospital. This project was an interdisciplinary endeavor, led by the CNS and nurse manager, which combined early extubation protocols with enhanced rounding initiatives to help decrease overall length of ventilation time as well as reduce pulmonary complications in patients in the cardiac surgery intensive care unit. The project resulted in a significant decrease in length of stay and a decrease in pulmonary complications in the postoperative period.